INVESTIGATING HOW THE NATIONAL ONLINE MEDIA REPORTED THE LGBT COMMUNITY DURING THE COVID-19 PANDEMIC - Isni Hindriaty Hindarto (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
At the beginning of the Covid-19 pandemic, intolerance against sexual minority groups (SMGs) were recorded in online media. SMGs were accused of spreading the coronavirus. This study aimed to determine the extent to which online media took sides in reporting LGBT issues during the first year of the pandemic. News balance analysis was performed using the “Westerstahl” Concept of objectivity for the coverage of Republika, CNN, and Kompas online. The measurement of media balance was carried out by employing the content analysis method that is used forsame-topic news, which also measures the sources of bias, news tendencies, and source’s representation. Previous research suggested that Republika chose to highlight LGBT’s negative sides. The results of the present study negate this assumption. It was also found that there was no discrimination against SMGs as has often been claimed in the comments on social media. This result may not be surprising for Kompas or CNN. It can even be said that when the outbreaks began, no media coverage associated the pandemic with SMG discrimination. The imbalance was found not in the online news pages but in what the viewers who chose to offer comments concerning the imbalance in LGBT news on social media had to say. At the same time, reader hesitation about offering comments on online media forums is interesting and calls for further research.